Autobiographical Memory and Future Thinking Specificity and Content in Chronic Pain - Quenstedt, Stella R.; Sucher, Jillian N.; Pfeffer, Kendall A.; Hart, Roland; Brown, Adam D. (Frontiers in Psychology, 2021)
Chronic pain is associated with high levels of mental health issues and alterations in cognitive processing. Cognitive-behavioral models illustrate the role of memory alterations (e.g., autobiographical memory and future thinking) in the development and maintenance of chronic pain as well as in mental health disorders which frequently co-occur with chronic pain (e.g., anxiety and mood disorders). This study aims to expand our understanding of specific cognitive mechanisms underlying chronic pain which may in turn shed light on cognitive processes underlying pain-related psychological distress. Individuals (N=84) who reported a history of chronic pain and individuals who reported no history of chronic pain (N =102) were recruited from MTurk to complete an online survey including standardized measures of anxiety and depression and two sentence completion tasks that assessed autobiographical memory and future thinking specificity and content. Chi square analyses revealed that participants who endorsed experiencing chronic pain were significantly more likely to recall at least one painful and negative event and to imagine at least one anticipated painful event in their future. Two ANCOVAs were performed to examine the degree to which chronic pain endorsement influenced specificity in memory and future imagining. Individuals with a history of chronic pain and higher levels of depression symptom severity generated autobiographical memories with significantly less specificity; whereas, individuals with a history of chronic pain also generated future autobiographical events with significantly less specificity. In addition, individuals with a history of chronic pain were more likely to generate episodes related to pain when asked to recall the past or imagine the future. Further research is needed to improve our understanding of the etiology of autobiographical memory and future thinking specificity and content in the pathogenesis of mental health conditions in the context of chronic pain.